Stabilization of aeolian sand with combined use of geofiber and synthetic fluid - Kenan Hazirbaba (Taylor & Francis Group, 2019)
Aeolian sand is very common in arid and semi-arid regions. Without proper improvement, this soil lacks desirable engineering characteristics for use for pavement base courses, subbase courses, subgrades, and as a foundation supporting layer under buildings. A non-conventional soil stabilization technique combining synthetic fluid and geofiber as improvement additives were investigated through an extensive and systematic experimental study. Engineering characteristics of various soil-additive compositions were evaluated through CBR and large-scale direct shear tests. Beneficial effects of the additives in terms of both the CBR performance and shear strength of aeolian sand were discovered. Proper additive dosages and curing of the treated soil were found to play a significant role in achieving the desired improvemen/Asphaltt of the CBR value and peak friction angle. Comparative analysis between peak and post-peak strength of various soil/additive compositions is presented. As part of the results of this study, a relatively strong correlation between CBR and internal friction angle was established.